Baseline report on the evaluation of 'Familias en Accion' - Orazio Attanasio; Claudia Benavides; Catalina Borda; Carlos Castro; Maria Elvira Carvajal; Luis Carlos Gómez; Ana Gómez; Luis Fernando Gómez; Santiago Grillo; Martha Isabel Gutiérrez; Rodolfo Heredia; Jhon Jairo Romero; et al. (Institute for Fiscal Studies (IFS), 2004)
This report describes the survey that was carried out in 122 communities in rural Colombia bythe consortium formed by the Institute for Fiscal Studies, Econometria and SEI as the baselinefor the impact evaluation of Familias en Acción, a programme to foster the accumulation of human capital in rural Colombia, run by the Colombian government.
Keywords: 330